Oxidative Stress Mediates the Association between Thyroid Dysfunction and Breast Cancer - Maira Mahmood; Mazhar Mushtaq; Aamenah Malik; Rukhshan Khurshid; Faiza Aamir; Arham Javed (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Breast Cancer (BC) and thyroid dysfunction are commonly observed ailments in females, and two may occur synchronously. The present study was conducted to find the role of oxidative stress and its association with thyroid dysfunction and BC.METHODS: In this cross-sectional study, 288 and 100 subjects were included in case and control groups, respectively. Serum samples were obtained from consented subjects. Thyroid profile, thyroid antibodies, antioxidant and oxidant profiles, as well as cathepsin S (CTSS), prolactin, and estradiol levels were estimated using specific enzyme-linked immunosorbent assay kits. The data was analyzed using independent Student's t-test and Pearson correlation test.RESULTS: BC cases had higher levels of thyroid antibodies and thyroid stimulating hormone than controls. Prolactin and estradiol levels were also deranged in the case group. Higher oxidative stress biomarkers were evident in the case group; 8-hydroxy-2'-deoxyguanosine (8-OHdG), a DNA damage marker, increased concomitantly. Correlation analysis showed a positive correlation between the antioxidant (catalase) and the oxidant (8-OHdG) levels. Furthermore, the higher level of CTSS in BC cases than in the controls is the hallmark of this study, demonstrating the pathogenesis and progression of the disease.CONCLUSION: Results suggest the mediating role of oxidative stress in the association between thyroid dysfunction and BC. It concludes that the parameters assessed in this study could be indicative of disease progression and metastasis in BC as well as thyroid dysfunction.KEYWORDS: breast cancer, thyroid, oxidant, antioxidant, ROS